Changes in Physical Health-Related Indexes of Delhi NCR school students post COVID-19 lockdown. - Divyam Sharma; Tithi Das; Megha Yadav (Revista Electronica de Veterinaria, 2024)
Background: The COVID-19 pandemic and resulting lockdowns have impacted physical health and activity levels globally, particularly among school children. This study aims to examine the effects of COVID-19 infection and obesity on various physical health-related indices among students aged 15-17 years in Delhi NCR.Objective: The objective of the study is to evaluate differences in body mass index (BMI), flexibility, explosive strength, muscle strength, and cardiorespiratory endurance between COVID-19 affected and unaffected students, and between obese and non-obese students.Methods: This was a comparative study conducted on 80 school students aged 15-17 years using simple convenient sampling. The students were divided into four groups: (1) Obese and COVID-positive, (2) Obese and COVID-negative, (3) Non-obese and COVID-positive, and (4) Non-obese and COVID-negative. The outcome measures included BMI, flexibility, explosive strength, muscle strength, and cardiorespiratory endurance. Data analysis was performed using independent t-tests to compare physical health-related indices, with IBM SPSS Statistics Viewer version 21.Results: No significant differences were observed between COVID-19 affected and unaffected students in any of the physical health-related indices. However, significant differences were found between obese and non-obese students in BMI (p = 0.000) and flexibility (p = 0.000). There were no significant differences in explosive strength (p = 0.187), muscle strength (p = 0.076), or cardiorespiratory endurance (p = 0.001) between the groups.Conclusion: COVID-19 infection did not show a significant lasting impact on the physical health indices of students. However, obesity was linked with higher BMI and decreased flexibility. Obese students exhibited comparable explosive strength and muscle strength to non-obese students but should be encouraged to engage in activities that enhance physical activity and flexibility for improved long-term health outcomes.